CBL mutations in chronic myelomonocytic leukemia often occur in the RING domain with multiple subclones per patient: Implications for targeting - Lim, Kelly; Kan, Winnie L.; Nair, Pramod C.; Kutyna, Monika; Lopez, Angel F.; Hercus, Timothy; Ross, David M.; Lane, Steven; Fong, Chun Yew; Brown, Anna; Yong, Agnes; Yeung, David; et al. (PLOS ONE, 2024)
Chronic myelomonocytic leukemia (CMML) is a rare blood cancer of older adults (3 in every 1,000,000 persons) characterized by poor survival and lacking effective mutation-specific therapy. Mutations in the ubiquitin ligase Cbl occur frequently in CMML and share biological and molecular features with a clonal disease occurring in children, juvenile myelomonocytic leukemia (JMML). Here we analyzed the clinical presentations, molecular features and immunophenotype of CMML patients with CBL mutations enrolled in a prospective Phase II clinical trial stratified according to molecular markers. Clinically, CBL mutations were associated with increased bone marrow blasts at diagnosis, leukocytosis and splenomegaly, similar to patients harboring NRAS or KRAS mutations. Interestingly, 64% of patients presented with more than one CBL variant implying a complex subclonal architecture, often with co-occurrence of TET2 mutations. We found CBL mutations in CMML frequently clustered in the RING domain in contrast to JMML, where mutations frequently involve the linker helix region (P<0.0001). According to our comparative alignment of available X-ray structures, mutations in the linker helix region such as Y371E give rise to conformational differences that could be exploited by targeted therapy approaches. Furthermore, we noted an increased percentage of CMML CD34+ stem and progenitor cells expressing CD116 and CD131 in all CBL mutant cases and increased CD116 receptor density compared to healthy controls, similar to CMML overall. In summary, our data demonstrate that CBL mutations are associated with distinct molecular and clinical features in CMML and are potentially targetable with CD116-directed immunotherapy.